The effectiveness of combined resection and radiotherapy for primary pineal malignant melanoma: a systematic review - Zhang, Jibo; Wei, Zixuan; Chen, Jincao (Frontiers in Neurology, 2024)
To evaluate the effectiveness of combined resection and radiotherapy (CRAR) for primary pineal malignant melanoma (PPMM)Relevant studies were identified through a literature search in PubMed, Embase and Web of Science from 1899 to September 1, 2023. Then we further screened the literature according to the updated PRISMA 2020 guidelines. The article information, patient information, treatment and survival rate were analyzed. The primary outcome measures the survival rate of CRAR compared with the overall patients and the patients without treatment. Secondary outcome measures operation methods, radiotherapy methods and dose.28 published articles were recorded. Among them, there were 35.71% (10/28) articles on CRAR. The median overall survival, CRAR and no treatment survival were 65, 88 and 12 weeks, respectively. The median overall survival of CRAR obviously better than that of no treatment (P<0.0001) and overall survival, even through P=0.1177. Most of the operations were supracerebellar infratentorial approach, and stereotactic radiation to tumor bed with usually range between 50 and 60 Gy, small dose and multiple fractions was the most popular radiotherapy method.So far, CRAR, compared with other treatments, is more beneficial to prolong the survival of PPMM patients. But the best approach for treatment needed plenty of clinical cases to verify in the future.